ANCIENT SOGDIANA - Seytimbetov Minsizbay Kazakbaevich; Otarbaeva Malika Ongarbaevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article is about ancient Sogdiana, the beginning of the history of its statehood is determined. At the same time, ancient historical monuments of Sogdiana, ethno-cultural similarities with Bactria, Margiana are shown.